Impact toughness, hardness and shear strength of Fe and Bi added Sn-1Ag-0.5Cu lead-free solders - Ali, B.; Sabri, M.F.M.; Jauhari, I.; Sukiman, N.L. (Elsevier, 2016)
In this study, the new Fe/Bi-bearing Sn-1Ag-0.5Cu (SAC105) solder alloys were studied for their mechanical properties, including impact toughness, hardness and shear strength. Charpy impact tester with impact speed of 5.4 m/s was used to determine the impact absorbed energy during impact tests. With the 0.05 wt.% Fe and 1 wt.% Bi addition to the SAC105 alloy, the impact absorbed energy increased from 8.1 J to 9.7 J by about 20% and literally no further improvement was observed by increasing the Bi content in the alloy. Vickers hardness tests were performed with a load of 245.2 mN and load dwell time of 10 s. The addition of Fe/Bi to SAC105 increased the hardness of the alloy from 10.5 HV to 22.6 HV showing an increase of more than two fold. Shear tests were performed with a shear speed of 0.25 mm/min. Shear strength almost doubled for the Fe/Bi added SAC105, as compared to the base alloy, increasing from 17.8 MPa to 34.3 MPa. The microstructure study shows that Bi is dissolved in the solder bulk and strengthens the solder alloys by its solid solution strengthening mechanism. The β-Sn grain size, as revealed by cross-polarized optical microscopy, significantly reduced from 60–100 μm to 20–40 μm with Fe/Bi addition to SAC105. The micrographs of field emission scanning electron microscopy (FESEM) with backscattered electron detector and their further analysis via ImageJ software indicated that Fe/Bi addition to SAC105 significantly reduced the Ag3Sn and Cu6Sn5 IMCs size and refined the microstructure. These changes in the microstructure of Fe/Bi added SAC105 expectedly resulted in such improvement in their mechanical properties.